The crystal structure of Thermus thermophilus UMP kinase complexed with a phosphoryl group acceptor and donor - Kenji Fukui; Anzu Nishiwaki; Noriko Nakagawa; Seiki Kuramitsu; Ryoji Masui (PLoS ONE, 2025)
Nucleoside monophosphate kinases play crucial roles in biosynthesis and regeneration of nucleotides. Prokaryotic UMP kinase belongs to a family of amino acid kinases but not to other nucleoside monophosphate kinases. Although many structures of prokaryotic UMP kinase have been determined, limited structural information has been available on the conformational changes along the reaction and allosteric pathways. We determined the crystal structure of UMP kinase of an extreme thermophile Thermus thermophilus HB8 in ADP-UDP–bound form at 2.6-Å resolution. The structure of the ADP-UDP complex is the first structure of bacterial UMP kinase with a phosphoryl group donor and an acceptor. Upon simultaneous binding of ADP and UDP, the loop near ADP moved toward the active site without global open-closed conformational changes, compared to the ligand-free and UDP-bound forms. Such a shift was not observed for archaeal UMP kinases but had some similarities to those in other amino acid kinase families of enzymes.